2009
DOI: 10.1097/gme.0b013e318199e734
|View full text |Cite
|
Sign up to set email alerts
|

Twice-weekly synthetic conjugated estrogens vaginal cream for the treatment of vaginal atrophy

Abstract: A low dose (1 g = 0.625 mg) of SCE-A vaginal cream administered twice weekly was shown to be effective compared with placebo in treating VVA in postmenopausal women for the three coprimary efficacy measures of maturation index, pH, and severity of the MBS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 6 publications
3
30
1
Order By: Relevance
“…36 Treatment with 0.005% estriol vaginal gel improved dyspareunia in the great majority of women (86.5%), a finding that is consistent with the described effect of estrogens on this symptom (70%-90%) 21,34,37 ; however, the placebo gel also produced a positive effect in an important subset of women and the comparison between groups was close to statistical significance (P = 0.095). This result may be justified by several reasons, mainly by the fact that dyspareunia was not set as primary endpoint of this clinical trial and was not considered for sample size calculation, hence the study is underpowered for the evaluation of this variable.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…36 Treatment with 0.005% estriol vaginal gel improved dyspareunia in the great majority of women (86.5%), a finding that is consistent with the described effect of estrogens on this symptom (70%-90%) 21,34,37 ; however, the placebo gel also produced a positive effect in an important subset of women and the comparison between groups was close to statistical significance (P = 0.095). This result may be justified by several reasons, mainly by the fact that dyspareunia was not set as primary endpoint of this clinical trial and was not considered for sample size calculation, hence the study is underpowered for the evaluation of this variable.…”
Section: Discussionsupporting
confidence: 83%
“…Additionally, a very high placebo effect on dyspareunia was observed, a finding that is in agreement with published data that show a particularly high placebo effect when symptoms of postmenopausal vaginal atrophy are studied (improvements in 30%-66% of women). 8,10,34,35,38,41 Moreover, the placebo effect is expected to be particularly higher in this study, as the 0.005% estriol vaginal gel was formulated as a highly hydrating gelVto confer a supplementary effect that could be of importance in certain circumstances such as the beginning of the treatmentVand in this sense, the placebo is more than an inert treatment. Finally, estrogen deficiency is unlikely to be the sole cause of dyspareunia in postmenopausal women 42<44 ; thus, it must be admitted that the dyspareunia expressed by some of the women may have been due to other causes (functional, psychogenic dyspareunias) not thoroughly assessed in the protocol in which estrogens would not be a more effective treatment than placebo itself.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Therefore, our study does not support a methyltestosterone aromatization hypothesis at the doses given. The reduction in vaginal pH and increase in vaginal maturation index observed in this study are similar to those in studies reported in patients with vulvovaginal atrophy treated with vaginal estrogen cream (14)(15)(16).…”
Section: Figuresupporting
confidence: 93%
“…A vaginal cream containing plant-derived synthetic conjugated oestrogen A has been evaluated in a randomised placebo controlled study involving 305 women for 12 weeks [16]. Synthetic conjugated estrogens A contains nine synthetic estrogenic substances.…”
Section: Synthetic Conjugated Estrogensmentioning
confidence: 99%